PENGARUH KOMPETENSI DAN PEMBERIAN INSENTIF TERHADAP PRODUKTIVITAS KERJA SALESMAN (Kasus Distributor Mobil Toyota PT.Agung Automall Soekarno-Hatta Pekanbaru) Effect of competence and granat of incentive to work productivity salesman (Case distributor PT.Ag - Surya Ningsih Sinaga; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study to determine the effect of competence and incentives to work productivity salesman PT.Agung Automall Soekarno-Hatta Pekanbaru. Where the proposed two independent variables and the dependent variable, namely competence and incentives act as independent variables and labor productivity plays as the dependent variable. This study took a number of respondents as many as 32 people and the population in the salesman PT.Agung Automall Soekarno-Hatta pekanbaru. In this study, the data was obtained using a questionmaire with a scale of measurement using a Likert scale further processed and analyzed using the validity, reliabelitas, statistical analysis such as linear analysis, t test and f test using SPSS. Results of analysis using multiple liner regression, t test and f test so that it can be seen that he variable competence of a negative effect on work productivity salesman (H1), that incentives have a significant effect on the productivity of salesman (H2), and the significant influence of competence and administration incentives to work productivity salesman (H3) Keywords: competence, incentives, labor productivity